The Significance of Spatial Economics in Economic Education - Budner, Waldemar W. (Studia Oeconomica Posnaniensia, 2015)
The paper discusses the need for taking into account spatial economics, derived from the geographical research tradition, in the education of economists. It discusses the perception of space in the analysis of economic phenomena and processes and the role this plays in the education of economists. The analysis shows what scientific problems and what issues can and should be the subject of academic education. In addition, the paper defines the scope of interest for spatial economics and its relationships with related disciplines.